Effectiveness of Neem Leaves (Azadirachta indica) on Traumatic Ulcer Healing: A Literature Review - Atha Syakirah; Talitha Edra Clayrine Siregar; Sutansyah Rakha Putra; Zalwa Nahrisya Askya; Mulya Duratun Nasha; Hafidhatun Annisa; Muhammad Ryan Triawan; Viona Diansari (PT Inovasi Pratama Internasional, 2026)
Traumatic ulcer is the most common oral mucosal lesion encountered in dental practice, caused by mechanical, thermal, or chemical trauma. This condition causes significant pain and can impair patient quality of life. Neem leaves (Azadirachta indica) have long been used in traditional medicine as anti-inflammatory, antibacterial, and wound-healing agents. This literature review aims to examine scientific evidence on the effectiveness of neem leaves in healing traumatic ulcers through their pharmacological mechanisms. Literature searches were conducted through PubMed, Google Scholar, and Science Direct databases with keywords related to neem leaves, Azadirachta indica, traumatic ulcer, and oral mucosal wound healing. Articles meeting the inclusion criteria were critically reviewed. Active compounds in neem leaves including nimbin, nimbidin, azadirachtin, quercetin, and tannins have been proven to possess anti-inflammatory activity by inhibiting COX-2 and NF-κB pathways, as well as antibacterial activity against oral pathogenic bacteria. These compounds also accelerate fibroblast proliferation and collagen synthesis crucial in wound healing. Neem leaves have significant potential as a therapeutic agent in healing traumatic ulcers based on pharmacological evidence and preclinical studies. However, further randomized controlled clinical trials are needed to strengthen their clinical use